shared influence of phylogeny and ecology on the reproductive patterns of Myrteae (Myrtaceae) - Staggemeier, Vanessa Graziele; Diniz-Filho, José Alexandre Felizola; Morellato, Leonor Patrícia Cerdeira (The Journal of ecology, 2010)
1. Many factors shape plant reproductive patterns including climate, competition or attraction of pollinators and seed dispersers, flower and fruit morphologies and phylogenetic relationships. South American Myrtaceae (Myrteae) were chosen to evaluate hypotheses on how abiotic and biotic factors, morphology and phylogeny influence plant reproductive phenology. 2. We examined whether Myrteae reproductive patterns are seasonal and related to climate; whether aggregated or segregated flowering and fruiting occur among species sharing pollinators or seed dispersers; the relationship between phenological and morphological traits, time of reproduction and Myrteae phylogenetic history; and the shared influence of ecological (environmental) and phylogenetic factors on Myrteae reproductive patterns. 3. We observed flowering and fruiting of 34 Myrteae species during 30 months in an Atlantic rain forest (south-eastern Brazil). We employed circular statistics to test for seasonality and multiple regressions to relate climate and phenology. Competition and facilitation hypotheses were tested using null models. We quantified the phylogenetic signal on phenology and morphology of Myrteae species using phylogenetic eigenvector regression (PVR) analyses, and used PVR and partial regressions to quantify the influences of ecology and phylogeny on phenology. 4. Myrteae flowered seasonally, whereas fruiting was not seasonal. Environmental factors (day-length and temperature) and associations with biotic vectors through facilitation hypothesis explained the aggregated blossom. Fruit maturation time affected the species' flowering sequence. Plants with longer fruit maturation times flowered at the end of the appropriate season, explaining the continuous fruit availability despite the seasonal flowering. The random fruiting pattern explained the regular presence of seed dispersers. Myrteae phenology was phylogenetically structured, even when phenophases were not seasonal, i.e., closer related species fruited under more similar environmental conditions, suggesting that the reproductive phenological niche was inherited along the course of evolution. We detected a shared influence of ecology and phylogeny on Myrteae phenological responses, and the ecological component explained better phenological variation than phylogeny. 5. Synthesis. We provided a new perspective on plant phenology based on phylogeny and ecology and demonstrated the importance of considering their shared influence in phenological studies. Our analyses can be employed for the most representative families of highly diverse ecosystems to improve our understanding of evolutionary patterns and general trends in phenology.